Education and career planning open course - Shier, Mary; Schubert, Allison; BC Open Textbook Project; BCcampus (BCcampus, BC Open Textbook Project, 2018)
"This online course, Education and Career Planning, is a unique open course which is the result of a collaboration between 7 colleges and BCcampus Open Education. It is at the provincial ABE level (grade 12 equivalent) and can be used as an elective course towards the BC Adult Grad Diploma. It enables colleges to offer the course on their platforms, use their own instructors, and earn their own FTE's. The course includes learning modules, student activities and assignments. The goal of Career Planning is to enhance the life and employment readiness skills of adult learners. Students will be prepared to pursue occupational and educational goals in a changing and diverse world. The topics include career exploration, communication skills, personal awareness, living skills, job search, interpersonal skills, and career management. The course can be downloaded into a learning management system such as Moodle or Desire2Learn using the files available below. The Common Cartridge file can be used for LMS systems other than D2L and Moodle. If you are need help importing the file, contact the IT support at your instutution. Gina Bennett, Instructional Designer, and Gordon Shier, Lead Illustrator"--BC Campus website.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from BC Campus website (viewed on January 24, 2018).
Keywords: Career development; Vocational guidance; Electronic books